A Hervadian Realistic Argument for the Juridical Status of Natural Law - Popović, Petar (Ius ecclesiae, 2019)
This paper addresses the question of the juridical status of natural law from th epoint of view of Javier Hervada's re-reading of the classical juridical realism. The contribution to the topic of some of Hervada's intellectual followers, like Carlos José Errázuriz and Eduardo Baura wil also be consulted. It will be argured that a Hervadian account of the juridical status of natural law is contextualized within the Spanish jurist's doctrine on the twofold aspect - motral on his argument on the natural title of right. We shall subsequently show that the juridical - of the legal norm and on his argument on the natural title of right. We shall subsequently show thar the juridicity of natural law is founded upon a clear distinction - without separacion - between the mora! and juridical status of natural law. The essential properties of the juridical status of natural law will be presented along with the treatment of the reconstitution of the natural human goods as natural juridical goods. A reference will also be made to the structure of the precepts of juridical natural law precisely as "natural" norms.